UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MEMANFAATKAN PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR DENGAN MENERAPKAN METODE DISKUSI KKG DI SDN GERIH 1 KECAMATAN GERIH KABUPATEN NGAWI TAHUN 2018-2019 - Purnami Purnami (Jurnal Paradigma, 2022)
The purpose of this research is to improve teachers' ability to use the school library as a learning resource through discussions in the Teacher Working Group (KKG) at SDN GERIH 1. Teachers can perfect the learning methods applied in schools so as to increase creativity, motivation and student learning outcomes. This research was designed in the form of School Action Research which was planned to be carried out in two cycles, where each cycle was carried out in two to three meetings. The subjects of this study were teachers at SD Negeri GERIH 1 consisting of 9 class teachers.In the first cycle the average value obtained from the attitude of the teacher discussing the discussion was 78.89 in the "enough" category, while in the second cycle the average value obtained was 86.78, the "good" category, the average value obtained from the assessment of the learning scenario in cycle I was 78.33 in the "enough" category while in cycle II the average value obtained was 84.44, the average value obtained from the assessment of the implementation of learning in cycle I was 69.67 in the "enough" category , while in cycle II the average value obtained was 83 in the "good" category. Based on the success mentioned above, it is suggested to teachers at SD Negeri GERIH 1 to further optimize the use of the school library as a source of learning by increasing the variety of learning methods in preparing learning scenarios and in implementing learning.